Potent Antidiabetic Activity of Ethanolic Extract of Terminalia Arjuna Fruits on Streptozotocin-Induced Diabetic Wistar Albino Rats: Pharmaceutical Science-Pharma - Adlak, Pradeep; Sagar, Rakesh; Lal Kori, Mohan (International Journal of Life Science and Pharma Research, 2022)
Diabetes mellitus is the most common chronic endocrine and metabolic disorder, impacts the quality of life, and has become the leading cause of death worldwide. Now a day’s, herbal drugs are in great demand for the treatment of diabetes because of their traditional acceptability, lesser side effects, and adverse effects compared with allopathic medications. Terminalia arjuna fruits were selected for the study due to their abundant availability and based on ethanomedicinal folk claims. The fruits of Terminalia arjuna have been evaluated for their antidiabetic and antihyperlipidemic activities using streptozotocin-induced diabetic Wistar albino rats. In the study, two doses of ethanolic extract of Terminalia arjuna fruits (TAF) were selected and administered to normal rats for an oral glucose tolerance test. For an antidiabetic study in streptozotocin-induced diabetic rats, the effect of the extract was observed for 28 days for blood glucose alterations. All experimental animals were observed for weight changes, due to STZ-induced diabetes, and were found to be significantly reverted to normal in all animals except the diabetic control group. After the completion of the experimental period, the collected serum samples were subjected to various biochemical parameters studied, including a lipid profile, glycosylated hemoglobin (HbA1c), urea, and creatinine level. An antioxidant study was performed using collected tissues, followed by histopathological studies of the pancreas. The research study revealed that the TAF extract has significant antidiabetic activity and the potential to revert the altered lipid profile and increase HbA1c to normal. TAF extract significantly normalized the urea, creatinine, superoxide dismutase, catalase, and glutathione peroxidase levels. Thus, the study concluded that TAF extract exhibits significant (p>0.05) antidiabetic activity in STZ-induced diabetic rats.